2017
DOI: 10.1177/1056492616688086
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Responses to Proto-Institutions: How the Semi-edited and Unedited Accounts Clash

Abstract: While adoption of institutionalized structures has received immense attention from organizational scholars, the processes associated with adoption of proto-institutions are infrequently studied. Drawing on an ethnographic longitudinal study of Producer Choice adoption by a public broadcasting organization, I contribute to the extant literature by offering three findings. First, I show how the semi-edited account of an initial implementation of proto-institution clashes with multiple unedited accounts of subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 120 publications
0
6
0
1
Order By: Relevance
“…For instance, the Japanese permanent employment institution had to yield to economic pressures (Ahmadjian and Robinson, 2001) and the established institutions regulating Norwegian fisheries were changed by government intervention (Holm, 1995). At the other end of the spectrum, it can easily be noticed that some proto-institutions (Hensel, 2018; Lawrence et al, 2002; Zietsma and McKnight, 2009) do become institutionalized. Such developments can be explained by pointing to numerous causes such as external shocks (Meyer, 1982), agency of institutional entrepreneurs (DiMaggio, 1988), practice-driven change (Smets et al, 2012), and competition of institutional logics (Dunn and Jones, 2010; Thornton et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Japanese permanent employment institution had to yield to economic pressures (Ahmadjian and Robinson, 2001) and the established institutions regulating Norwegian fisheries were changed by government intervention (Holm, 1995). At the other end of the spectrum, it can easily be noticed that some proto-institutions (Hensel, 2018; Lawrence et al, 2002; Zietsma and McKnight, 2009) do become institutionalized. Such developments can be explained by pointing to numerous causes such as external shocks (Meyer, 1982), agency of institutional entrepreneurs (DiMaggio, 1988), practice-driven change (Smets et al, 2012), and competition of institutional logics (Dunn and Jones, 2010; Thornton et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They are usually emotionally and symbolically charged, and whether they will develop into a full story has much to do with power relations and issues of legitimacy and credibility (Gabriel, 2016). Protostories may relate to proto-institutions (Lawrence, Hardy, and Phillips, 2002) and serve as accounts that determine proto-institutions' development into institutions (Hensel, 2018).…”
Section: Why Decision Making Through Stories? Varieties Of Instantiat...mentioning
confidence: 99%
“…Since inter-institutional projects often follow the same formula when they involve the same actors within wider lines of projects or portfolios of projects, this definition opens the possibility to approach inter-institutional projects as permanent or recurring proto-institutions. Hensel (2018) suggested that actors can adopt protoinstitutions to imitate highly legitimate actors in their field in an effort to increase their own legitimacy. For example, this can include new fashionable practices not yet institutionalized but that might carry existing institutional logics with a higher potential of institutional plasticity.…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%